2014
DOI: 10.1371/journal.pone.0083488
|View full text |Cite
|
Sign up to set email alerts
|

Confidence and the Stock Market: An Agent-Based Approach

Abstract: Using a behavioral finance approach we study the impact of behavioral bias. We construct an artificial market consisting of fundamentalists and chartists to model the decision-making process of various agents. The agents differ in their strategies for evaluating stock prices, and exhibit differing memory lengths and confidence levels. When we increase the heterogeneity of the strategies used by the agents, in particular the memory lengths, we observe excess volatility and kurtosis, in agreement with real marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 26 publications
1
44
0
5
Order By: Relevance
“…Lengnick et al (2013) develop a monetary ABM and confirm that the interbank market improves macroeconomic stability in normal times but serves as a shock amplifier in times of financial malaise. Bertella et al (2014) find that with high investor heterogeneity their stylized financial ABM shows excess volatility and kurtosis, similar to real market fluctuations. Bargigli et al (2014) analyze the effects of leverage-and network-accelerators in the macro ABM of Riccetti et al (2013), and find that improved economic activity implies a denser network at the cost of increased leverage and increased concentration in the banking sector.…”
Section: Introductionmentioning
confidence: 77%
“…Lengnick et al (2013) develop a monetary ABM and confirm that the interbank market improves macroeconomic stability in normal times but serves as a shock amplifier in times of financial malaise. Bertella et al (2014) find that with high investor heterogeneity their stylized financial ABM shows excess volatility and kurtosis, similar to real market fluctuations. Bargigli et al (2014) analyze the effects of leverage-and network-accelerators in the macro ABM of Riccetti et al (2013), and find that improved economic activity implies a denser network at the cost of increased leverage and increased concentration in the banking sector.…”
Section: Introductionmentioning
confidence: 77%
“…For instance, Bertella et al found the excessive volatility of asset price in the established artificial market with an increase in heterogeneity of the strategies chosen by agents from Ref. [5]. As discussed by Bertella et al [5], Yim et al [6] further developed the agent-based model to reveal the nonlinear interaction among heterogeneous agents, which could be regarded as "stylized facts" occurred in financial market.…”
Section: Related Studiesmentioning
confidence: 99%
“…[5]. As discussed by Bertella et al [5], Yim et al [6] further developed the agent-based model to reveal the nonlinear interaction among heterogeneous agents, which could be regarded as "stylized facts" occurred in financial market. In this model, agents included three types of participants: optimist, pessimist and fundamentalist.…”
Section: Related Studiesmentioning
confidence: 99%
“…The price formation will follow the price adjustment method [35][36][37][38]. The price adjustment process achieves local price equilibrium in the market based on the aggregate bids and offers…”
Section: Definitionmentioning
confidence: 99%